Takhrij and Syarah Hadith of Chemistry: The Nutrient Content of Zam-Zam Water - Wulida Ullya Adzinta; Siti Nur Amelia; Nunung Kurniasih; Saifudin Nur; Dodo Widarda (UIN Sunan Gunung Djati Bandung, 2021)
This research aims to discuss the hadith of Prophet Muhammad SAW. about content of zam-zam water. The research method used in the processing of takhrij and syarah hadith is a qualitative method with chemical analysis. The result and discussion of this research is that is zam-zam water is water that appeared during the period of Prophet Ismail AS. This water is believed to have many miracles and properties. There are several substances contained in zam-zam water, including sodium, magnesium, calcium, potassium, fluoride, and others. This water can also help cure various diseases. After analyzing iron content, it was found that the Fe concentration was 0,0599 mg/l at a wavelength of 248,3 nm, it is meaning this water is suitable for consumption in accordance with the drinking water standards of the Minister of Health.